2018
DOI: 10.1080/13543776.2018.1549229
|View full text |Cite
|
Sign up to set email alerts
|

A patent review of the ubiquitin ligase system: 2015–2018

Abstract: Introduction: Ubiquitin-Proteasome System (UPS) has been validated as a novel anticancer drug target in the past 20 years. The UPS contains two distinct steps: ubiquitination of a substrate protein by ubiquitin activating enzyme (E1), ubiquitin conjugating enzyme (E2), and ubiquitin ligase (E3), and substrate degradation by the 26S proteasome complex. The E3 enzyme is the central player in the ubiquitination step, and has a wide range of specific substrates in cancer cells, offering great opportunities for dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 140 publications
(173 reference statements)
0
36
0
Order By: Relevance
“…β-TrCP is an E3 ubiquitin ligase that regulates the expression of a variety of proteins 19 . YAP is phosphorylated by Hippo/LATS signaling kinase, causing YAP to remain in the cytoplasm 20 .…”
Section: Resultsmentioning
confidence: 99%
“…β-TrCP is an E3 ubiquitin ligase that regulates the expression of a variety of proteins 19 . YAP is phosphorylated by Hippo/LATS signaling kinase, causing YAP to remain in the cytoplasm 20 .…”
Section: Resultsmentioning
confidence: 99%
“…Our results demonstrated that HPV E7 promoted the ubiquitin-proteasome-mediated degradation of IFI16. The ubiquitin-proteasome system is mainly composed of ubiquitin-activating enzyme (E1), ubiquitin-crosslinking enzyme (E2), ubiquitin ligase (E3) and the 26S proteasome [32]. Among these components, the E3 ubiquitin ligase is responsible for target protein recognition and mediates the degradation of substrates by the 26S proteasome [33].…”
Section: Hpv E7 Interacts With Ifi16 and E3 Ligasetrim21mentioning
confidence: 99%
“…Some authors consider U-box (UFD2 homology) as a third subfamily. U-box ubiquitin-ligases act as scaffold proteins that recruit the ubiquitin-charged E2 enzyme and the substrate protein to docking sites [ 54 , 55 ]. Moreover, another novel family that shares features of RING and HECT is named RING-between-RING ligases (RBR).…”
Section: Molecular Mechanisms Of Emt In Cancer: Role Of Targeted Pmentioning
confidence: 99%